Muscarinic amplification of fast excitation in hilar neurones and inhibition in granule cells in the guinea-pig hippocampus - Brunner, Hans; Misgeld, Ulrich (The journal of physiology, 1994)
1. Effects of the cholinergic agonist, carbachol (CCh), or the acetylcholinesterase inhibitor, eserine, on presumed inhibitory hilar neurones and on inhibition in granule cells were studied by intracellular recording in guinea-pig hippocampal slices. 2. CCh (1-5 microM) strongly enhanced the discharge activity of hilar neurones and spontaneous and evoked IPSPs in granule cells. 3. Eserine, in an atropine-sensitive manner, increased the excitability of hilar neurones through effects on membrane properties and on excitatory synaptic barrage. EPSPs readily triggered long-duration burst discharges. In granule cells, the amplitudes of evoked GABAA and GABAB receptor-mediated IPSPs were enhanced. 4. In the presence of eserine and antagonists for glutamatergic and GABAergic synaptic transmission, train stimulation evoked atropine-sensitive slow EPSPs. In contrast to those in granule cells, slow EPSPs in hilar neurones were invariably preceded by a strong burst-after-hyperpolarization. 5. We suggest that acetylcholine, released from septo-hippocampal fibres, amplifies fast synaptic excitation of inhibitory hilar neurones and inhibition of granule cells. In the dentate area, muscarinic receptor-mediated effects are faster than anticipated from the time course of the slow EPSP.
Gesehen am 08.04.2021